Online Collaborative Writing and Interaction Patterns: A Case Study of Team Collaborations in the EFL Classroom - Kitjaroonchai, Nakhon; Suppasetseree, Suksan; Kitjaroonchai, Tanthip (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
This article reported a case study that investigated factors influencing interaction patterns in small group online collaborative writing tasks: description and argumentation. Participants included twelve Asian EFL university students formed into four teams of three members each. They were engaged in two online collaborative writing tasks via Google Docs spanning ten weeks. Data collection included the participants’ use of writing change functions and language functions during the online collaborative writing processes revealed through Google Docs revision history, collaborative essays, observations, student reflections, and semi-structured interviews. The findings revealed that the four teams exhibited divergent interaction patterns, but the patterns of interaction remained consistent within each group across both tasks. The qualitative content analysis revealed that effective team collaborations were driven by factors including mutual engagement in text contribution, scaffolding strategies, individual goals, learners’ English language proficiency, individual roles, and use of collaborative agency. The findings may help elucidate the divergence of online collaborative writing and provide insightful information for instructors to design online collaborative writing activities and assist EFL learners in co-construction of writing tasks. Keywords : EFL classroom, interaction patterns, case study